Adding to the Truth of the Matter: The Case for Qualitative Research. (October 2017) - Florczak, Kristine L.
The purpose of this column is to discuss the impact that qualitative research has on translational research, whose aim is to improve the health and well-being of individuals. To that end, rigorous qualitative research is examined; translational research is entertained and the manner in which qualitative research can be a co-equal partner with quantitative research is proposed.